1997
DOI: 10.1094/phyto.1997.87.3.353
|View full text |Cite
|
Sign up to set email alerts
|

Gene Flow and Sexual Reproduction in the Wheat Glume Blotch Pathogen Phaeosphaeria nodorum (Anamorph Stagonospora nodorum)

Abstract: Restriction fragment length polymorphisms (RFLPs) were used to characterize the genetic structures of three field populations of Phaeosphaeria nodorum from Texas, Oregon, and Switzerland. Data from seven nuclear RFLP loci were used to estimate gene diversity and genetic distances and to make indirect measures of gene flow between populations. Three of the seven RFLP loci differed significantly in allele frequencies across populations. On average, 96% of the total gene diversity was found within populations. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
65
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 19 publications
5
65
0
1
Order By: Relevance
“…In the absence of gene flow, genetic drift causes different allele frequencies at neutral loci, leading to differentiation in isolate populations (Keller et al 1997). The low genetic differentiation in this study has several possible explanations.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In the absence of gene flow, genetic drift causes different allele frequencies at neutral loci, leading to differentiation in isolate populations (Keller et al 1997). The low genetic differentiation in this study has several possible explanations.…”
Section: Discussionmentioning
confidence: 79%
“…2 Dendrogram of genetic relationships between seven populations of A. rabiei as reconstructed by UPGMA using Nei's genetic distance equilibrium, we can use GST to estimate Nm, the average number of migrants that would need to be exchanged among populations in each generation to account for their present lack of subdivision. Nm averaged 6.64 in all loci and populations, suggesting a level of gene flow that was 6 times greater than needed to prevent populations from diverging by genetic drift (Keller et al 1997). This result may help explain why resistance in new cultivars, periodically released by agricultural research centers and including material from the International Centre for Agricultural Research in the Dry Areas (INCARDA), has proven ineffective after 2-3 years (data not shown).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…S. nodorum survives on the field debris and is able to infest all above-ground plant organs of wheat. The major primary inoculum are the winddispersed ascospores (sexual form) in late autumn and early spring (Mittelstadt and Fehrmann 1987;Keller et al 1997a;Bathgate and Loughman 2001). During the growing season, particularly under wet and warm weather conditions, the asexually generated and rain-splashdispersed pycnidiospores successively infect different leaf levels of individual plants (Scharen 1966;Keller et al 1997a).…”
Section: Introductionmentioning
confidence: 99%
“…This higher pathogen density increases the likelihood of multi-infections in the same plant by different genotypes of the same pathogen (e.g. Linde et al 2002;Keller et al 1997;McDonald et al 1999). Multi-infections have long been thought to favor the development of higher virulence (defined here as the amount of damage done to the plant, but often referred to as aggressiveness or quantitative virulence in plant pathology) as a side effect of competition among strains for host resources (Van Baalen & Sabelis, 1995).…”
mentioning
confidence: 99%